Can athletes be tough yet compassionate to themselves? Practical implications for NCAA mental health best practice no. 4 - Stamatis, A.; Deal, P. J.; Morgan, G. B.; Forsse, J. S.; Papadakis, Z.; McKinley-Barnard, S.; Scudamore, E. M.; Koutakis, P. (PLOS ONE, 2020)
Recent tragic events and data from official NCAA reports suggest student-athletes' well-being is compromised by symptoms of mental health (MH) disorders. Self-compassion (SC) and mental toughness (MT) are two psychological constructs that have been shown effective against stressors associated with sports. The purpose of this study was to investigate SC, MT, and MH in a NCAA environment for the first time and provide practical suggestions for MH best practice No.4. In total, 542 student-athletes participated across Divisions (Mage = 19.84, SD = 1.7). Data were collected through Mental Toughness Index, Self-Compassion Scale, and Mental Health Continuum-Short Form. MT, SC (including mindfulness), and MH were positively correlated. Males scored higher than females on all three scales. No differences were found between divisions. SC partially mediated the MT-MH relationship, but moderation was not significant. Working towards NCAA MH best practice should include training athletes in both MT and SC skills (via mindfulness).